Eros Pinoy an anthology of contemporary erotica in Philippine art & poetry - Aviado, Virgilio; Cabrera, Benedicto; Yuson, Alfred A. (Anvil Publishing Inc., 2001)
The first anthology of Philippine erotic poetry and visual art, the book features over 70 poems and 80 artworks from 101 Filipinos writers and artists, including National Artists for Literature Edith Tiempo and Francisco Arcellana, and National Artists for Visual Arts Napoleon Abueva, Arturo Luz, Ang Kiukok, and J. Elizalde Navarro.